"Place standard" depicts social gradient in the neighbourhood environment in Cyprus. (30th September 2020) - Middleton, N; Kleopa, D; Kouta, C; Kaifa, S; Photiou, G; Panayioutou, A
Abstract: Background: Census data, GIS, surveys and audits are used to profile "place", each with shortcomings. There are several "neighbourhood environment" tools, including the "Place Standard" a policy and advocacy tool developed in Scotland. "Place" is not a strong feature in the public health agenda in Cyprus. Methods: In an internet survey under the auspices of the Cyprus Healthy Cities Office, participants rated 14 features of their neighborhood environment. Exploratory factor, cluster and regression analysis were used to explore the dimensionality of the concept, neighborhood profiles and differences according to individual and area-level characteristics. Results: With the exception of safety (M = 4.4, SD = 1.7 on a 1: large to 7: little improvement), 492 participants (mean age 42, 50% residents for >10 years) from 266 postcodes (33% islandwide) did not rate other features favourably, with lowest scores for "influence and sense of control". A clear dimensionality of Built, Physical, Social and Service environment supports the construct validity of the tool. People who rated their neighbourhood lower on a social position ladder were consistently more likely to rate all contextual neighrbourhood features less favourably. The social gradient was evident according to both individual sociodemographic characteristics and census-based area measures of built (e.g. pre-2001 housing) and socio-economic disadvantage (e.g. single-parent households) and appeared stronger in terms of the built (e.g. moving around) than the social environment (social contact, identity and belonging). Conclusions: The "place standard" shows good metric properties and can be used as a public health research, and practice tool to profile the variability and document the inequity in the neighbourhood health environment as well as to support and enhance citizens' participation in the dialogue, which they generally rate lowest. Key messages: The "Place Standard" offers a framework and a tool to profile the neighbourhood environment in research and public health practice. Generally unfavourable rating of health-related neighbourhood environment with evidence of social gradient across all features with larger differences in built environment.